Homegrown multimedia support program in enhancing the learning of oral presentation skills among UiTM Melaka pre-tesl students / Juritah Misman and G. Nagamany Govindan - Misman, Juritah; Govindan, G. Nagamany (Research Management Institute (RMI), 2010)
This experimental study explored at investigating the effectiveness of home-grown multimedia support material that highlights authentic use of oral presentations in the professional community. This study validated the hypothesis that TESL foundation students improved slightly their oral presentation skills by discussing and obtaining feedback from watching home-grown videos of content specific presenters. The results reflected that there is a slight improvement of presentation skills from the first presentation to the second oral presentation with the implementation of the home-grown multimedia support program. Also, results of the attitude questionnaires pertaining their general perspectives towards the effectiveness and the relevance of home-grown material reflected that almost all the respondents showed positive responses towards the use of multimedia support learning program. The study also revealed that authentic video recording showing real use oral skills in the professional world may motivate students to be aware of the real use presentations for authentic communication purposes. With the rising concern on ESP, English language practitioners are now moving towards getting the real world into the classrooms to make their teaching and learning experience more credible.